2010
DOI: 10.1375/jsc.5.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Asian Smokefree Communities: Evaluation of a Community-Focused Smoking Cessation and Smokefree Environments Intervention In New Zealand

Abstract: Language, culture and not knowing how to access services are barriers to the use of health services for Asian migrants. Asian Smokefree Communities (ASC) pilot-tested a novel Asian-specific service model to address these issues for Asian smokers. Korean- and Chinese-speaking coordinators delivered home-, workplace- or clinic-based interventions to support smokers with cessation and create smoke-free environments with families. A prior planned evaluation investigated the acceptability of the service, quit rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Even if they were aware of chewing tobacco practice and knew how to support cessation from chewing there are other barriers to access to be addressed. Language and cultural differences and not knowing how to access health and community services have been identified as barriers to accessing healthcare for South East Asian migrants in New Zealand (Wong et al, 2010). Even for stopping tobacco smoking, Asian people's use of the national free phone smoking cessation service, Quitline, is low.…”
Section: Discussionmentioning
confidence: 99%
“…Even if they were aware of chewing tobacco practice and knew how to support cessation from chewing there are other barriers to access to be addressed. Language and cultural differences and not knowing how to access health and community services have been identified as barriers to accessing healthcare for South East Asian migrants in New Zealand (Wong et al, 2010). Even for stopping tobacco smoking, Asian people's use of the national free phone smoking cessation service, Quitline, is low.…”
Section: Discussionmentioning
confidence: 99%
“…The most common community-oriented strategy, utilized in 18 (18/22, 82%) of the interventions, was the participation of community members in the development and implementation of service-level interventions. Members of the community health workforce were the most frequently represented in studies ( 16 20 ), followed by general community members ( 18 , 21 23 ) and community or church leaders ( 24 , 25 ). Other community members involved in these interventions were cancer survivors and family members of survivors ( 25 , 26 ), heart attack and stroke survivors ( 23 ), community volunteers ( 24 ), seniors/elders ( 17 ) and representatives ( 27 ), and clinicians from the target population ( 28 ).…”
Section: Cultural Competency Intervention Strategiesmentioning
confidence: 99%
“…Another commonly reported community-oriented strategy was the creation of community partnerships through the research process. Two studies identified taking a community-based participatory research (CBPR) approach ( 16 , 25 ); another identified using a community participation framework to guide the research ( 21 ); and a further two discussed the involvement of a community steering committee ( 29 ) or advisory board ( 30 ). Other studies discussed community involvement such as being initiated by community leaders and maintaining a strong community engagement focus ( 24 ), thereby establishing partnerships with key community groups and stakeholders ( 30 ) and collaborating with community health departments ( 23 ).…”
Section: Cultural Competency Intervention Strategiesmentioning
confidence: 99%
See 2 more Smart Citations